Síntese enzimática de ampicilina com diferentes substratos em reator integrado - Leite, Geísa de Abreu (2008)
Penicillin G acylase (PGA), EC 3.5.1.1.11, is an enzyme employed in the hydrolysis reactions of penicillin G to produce 6-amino penicillanic acid (6-APA), but it can also used in the synthesis of semi-synthetic antibiotics. This work investigated the influence of different biocatalysts conceptions and of different acyl donors on the ampicillin synthesis with immobilized PGA, determining experimentally yield data (antibiotic produced / consumed acyl donor), selectivity (antibiotic produced/D(-)-phenylglycine generated) and productivity (produced antibiotic (mmol)/UI/time). First of all, ampicilina synthesis were carried out in homogeneous solution (with substrates and products solubles), using industrial catalyst Recordatti, in order to verify the influence of the different acyl donors, D(-)- phenylgycine methyl (PGEM), ethyl (PGEE) and isopropyl (PGEI) esters on the synthesis of ampicillin. The results showed that the use of EEPG, besides not reducing the ampicillin synthesis rate, also it reduces the ester hydrolysis rate, showing great potential to increase the selectivity of the enzymatic route. The multipoint covalent attachment of PGA was carried out in agar-agarose support with medium diameter of 1.3 ± 7 × 10-2 mm. That biocatalyst was tested in the ampicillin synthesis at 25ºC with the methyl and ethyl esters, with the objective of evaluating its acting in two pH values (6.2 and 6.5). The ethyl ester presented the yield and selectivity (71 ± 4 and 2.2 ± 4 × 10-1) better than the phenylglycine methyl ester (67 ± 1 and 2.0 ± 1 × 10-1) being the pH 6,2 more favorable. Two different biocatalysts for use in the ampicillin synthesis with simultaneous crystallization of the products were tested: PGA immobilized within agarose particles with average diameter of 95.2 ± 3 × 10-1 μm and, soon after, wrapped by alginate gel, resulting in particles with average diameter of 2.1 ± 6 × 10-2 mm; and PGA immobilized in agarose ME particles (10% wt) with average diameter of 1.4 ± 8 × 10-2 mm. So much the envolvement of the immobilized enzyme by a secondary support (agarose-alginate catalyst) as the use of particles gel of millimetric dimensions (agarose 1.4 mm) caused modifications in the microambient of that enzyme, mainly in reason of the profiles of íons intra-particle generated with the progress of the reaction. In view of the above exposed, ampicillin synthesis were carried out in three different pHs (6.0; 6.2 and 6.5), at 25- °C, using the methyl, ethyl and isopropyl esters with excess of 6-APA. To reduce the hydrolyis of the produced antibiotic, making possible its industrial production, was necessary that it precipitates inside of the synthesis reactor. When we evaluated of global form the selectivity, yield and productivity we concluded that a promising strategy would be to carry out the synthesis using ethyl ester, alginate-PGA-agarose 6BCL catalyst in pH 6.2. By this condition was obtained productivity of 8.0 × 10-5 ± 8 × 10-6, selectivity 2.0 ± 2 × 10-1 and yield 62%. The reactions were also carried out with ester excess, however the selectivity was drastically reduced getting at 1.1 ± 6 × 10-2. The last stage of this work was the kinetic study of the ampicillin synthesis. Synthesis were carried out in several initial conditions of substrate concentration (6-APA and PGEE) in pH 6.0 and 6.2 with the alginate-PGA-agarose 6BCL catalyst. In some cases, ampicilin and D(-) -FG crystals were sowed in the reaction start to check possible inhibitory effects of the products. Largests yields and selectivities were obtained when the concentration of 6-APA was increased by the ester concentration. Inhibitory effect in the antibiotic hydrolysis was verified when a high concentration of both substrates was used. In general, the experiments carried out in heterogeneous medium favored the yield, selectivity and productivity. In all of the experiments the lowest pH (pH 6.0) favored the improvement of the yield and selectivity while the productivity was favored the pH 6.2. The synthesis in fed-batch reactor, with high concentration of substrates, favored the selectivity of the reaction, it passed from 2.5 to 3.5.